Synaptic plasticity of NMDA receptors: mechanisms and functional implications - Hunt, David L; Castillo, Pablo E (Current opinion in neurobiology, 2012)
► NMDARs exhibit diverse functional role based on their unique biophysical properties. ► We review current work describing activity-dependent plasticity of NMDAR transmission. ► NMDARs can by dynamically regulated by numerous induction and expression mechanisms. ► NMDAR plasticity is a powerful means by which information can be encoded and stored. Beyond their well-established role as triggers for LTP and LTD of fast synaptic transmission mediated by AMPA receptors, an expanding body of evidence indicates that NMDA receptors (NMDARs) themselves are also dynamically regulated and subject to activity-dependent long-term plasticity. NMDARs can significantly contribute to information transfer at synapses particularly during periods of repetitive activity. It is also increasingly recognized that NMDARs participate in dendritic synaptic integration and are critical for generating persistent activity of neural assemblies. Here we review recent advances on the mechanisms and functional consequences of NMDAR plasticity. Given the unique biophysical properties of NMDARs, synaptic plasticity of NMDAR-mediated transmission emerges as a particularly powerful mechanism for the fine tuning of information encoding and storage throughout the brain.